Liquid chromatographic tandem mass spectrometric assay for simultaneous quantification of compound 97/78 and its in vivo metabolite 97/63, a novel trioxane antimalarial, in human plasma and its application to a protein binding study - Kushwaha, Hari Narayan; Gautam, Nagsen; Singh, Shio Kumar (Arzneimittelforschung, 2011)
A sensitive, selective and specific LC-MS/ MS assay for simultaneous quantification of compound 97/78 and its active in vivo metabolite 97/63, a novel 1,2,4-trioxane antimalarial, in human plasma has been developed and validated using a-arteether as internal standard (IS). Extraction from plasma involves a simple protein precipitation method. The analytes were chromatographed on a Columbus C18 column with guard by isocratic elution with acetonitrile:ammonium acetate buffer (10 mM, pH 4.0) (80:20 v/v) as mobile phase at a flow rate of 0.45 mL min−1 and analyzed in multiple reactionmonitoring (MRM) positive ion mode. The chromatographic run time was 4.0 min. The weighted (1/×2) calibration curves were linear over a range of 1.56200 ng mL−1 with correlation coefficients > 0.998. For both analytes, the limit of detection (LOD) and lower limit of quantification (LLOQ) were 0.5 ng mL−1 and 1.56 ng mL−1, respectively. The recovery of 97/78, 97/63 and IS from spiked control samples were > 90% and their matrix suppression obtained were < 8%. The accuracy (% bias) and precision (% RSD) for both analytes were < 6.78%. Both analytes were stable after three freeze-thaw cycles (% deviation < 12.80), long-term for 30 days in plasma at −60 °C (% deviation < 14.38), for 8 h on bench top in plasma at ambient temperature (% deviation < 1.52) and also in the auto-sampler for 12 h (% deviation < 3.9%). The validated method was successfully applied to a protein binding study of compound 97/78 and metabolite 97/63 in human plasma. Furthermore, the validated method will be applicable to pharmacokinetics, bioavailability and metabolism in various clinical phases and in drug interaction studies.
Keywords: Antimalarial drug; Human plasma; LC-MS/MS; Metabolite; Protein binding; Stability